Dual-Wavelength Erbium Fiber Laser in a Simple Ring Cavity - Ahmad, Harith; Norizan, Siti Fatimah; Zulkifli, Mohd Zamani; Harun, Sulaiman Wadi (Taylor & Francis, 2009)
By controlling the cavity loss of the modes using a variable optical attenuator, specific intensities of distributed modes can be fed back into the erbium-doped fiber to produce signals without mode competition, thus resulting in stable lasing as a means to overcome mode competition in a homogenous gain medium. Two lasing signals were obtained with peak powers of approximately -3.475 dBm and -4.386 dBm for wavelengths of 1,540 nm and 1,548 nm, respectively, with a side mode suppression ratio of more than 43 dB.